In vitro Phenotype Induction of Circulating Monocytes: CD16 and CD163 Analysis - Karsulovic C; Tempio F; Lopez M; Guerrero J; Goecke A (Dove Medical Press, 2021)
Claudio Karsulovic,1,2 Fabian Tempio,3,4 Mercedes Lopez,3,4 Julia Guerrero,1 Annelise Goecke1,2 1Laboratorio de Inmunomodulación Neuroendocrina, Instituto de Ciencias Biomédicas, Facultad de Medicina, Universidad de Chile, Santiago, Chile; 2Seccion de Reumatología, Hospital Clínico Universidad de Chile, Universidad de Chile, Santiago, Chile; 3Laboratorio de Regulación e Inmunología del Cáncer, Facultad de Medicina, Universidad de Chile, Santiago, Chile; 4Instituto Milenio de Inmunología e Inmunoterapia, Facultad de Medicina, Universidad de Chile, Santiago, ChileCorrespondence: Annelise GoeckeSeccion de Reumatologia, Hospital Clínico Universidad de Chile, Universidad de Chile, Santos Dumont 999, Independencia, Santiago, ChileTel +56-229788000Email igoecke@hcuch.clIntroduction: CD14 (monocyte differentiation antigen, LPS binding protein – endotoxin receptor) and CD16 (FcγRIII, Low-affinity receptor for IgG) define three subpopulations of circulating monocytes with different inflammatory and phagocytic capabilities. Contradictory reports exist regarding both in vivo monocyte phenotype-disease association and response of these circulating monocytes to in vitro stimulation. We analyzed phenotypic changes in circulating monocytes when stimulated with LPS (pro-inflammatory stimulus) and IL-4 (alternative inflammatory stimulus).Methods: Mononuclear cells from nine healthy donors were extracted and studied for surface and intracellular markers using flow cytometry. PBMC were extracted using Ficoll technic and immediately analyzed using flow cytometry. Pro-inflammatory interleukin IL-1β and IL-6 were measured by intracellular cytometry. Mononuclear cells were stimulated using LPS and IL-4 as previously described. Changes against non-stimulated populations were statistically analyzed.Results: Compared to non-stimulated and IL-4 stimulated monocytes, LPS-stimulated cells display a singular pattern of markers, with higher levels of intracellular IL-1β and IL-6 directly correlating with CD14+CD163- cell frequency and diminishing membrane CD163 fluorescence. CD14+CD16- classical monocytes show greater percentage of CD163- cells upon LPS stimulation. CD86 levels on monocytes’ surface did not change with LPS or IL-4 stimulation.Conclusions and Discussion: We showed that CD14+CD16- classical monocytes display higher sensitivity to LPS stimulation, with more IL-1β and IL-6 levels than intermediate and non-classical monocytes. This subset also diminishes its CD163 levels on the membrane after LPS stimulation with a contemporary raise in CD163- cells, suggesting that classical monocytes preferentially acquire CD163- defined M1 characteristics upon in vitro LPS stimulation. Intermediate and non-classical monocytes respond with lower levels of interleukins and display surface proteins in an M2-type profile (CD163+).Keywords: classical, intermediate, non-classical, monocytes, phenotype, stimulation